Case Report: Endoscopic submucosal tunneling dissection using a golden knife for a giant gastric cancer lesion: a case report and literature review - Wu, Pan; Jin, Xi-Feng (Frontiers in Oncology, 2025)
BackgroundEndoscopic Submucosal Dissection (ESD) is a well-established technique for the removal of early gastrointestinal cancers. However, it is often perceived as time-consuming and carries a higher risk, particularly when dealing with larger lesions, especially those exceeding 3 cm in diameter. In this case report, we introduce the application of Endoscopic Submucosal Tunneling Dissection (ESTD) for the management of a substantial gastric superficial neoplasia, which encompassed a considerable area of early gastric cancer. Although there are several case reports detailing the use of ESTD for the resection of gastrointestinal cancers, there have been no documented instances of utilizing a “Golden Knife” specifically for the treatment of large gastric cancer lesions.Case presentationThis case report details the treatment of a 64-year-old male diagnosed with a large early-stage gastric cancer, measuring approximately 140 mm by 88 mm. The medical team opted for endoscopic submucosal tunneling dissection (ESTD) using a golden knife, a technique chosen for its effectiveness in managing such tumors. Following the procedure, pathological examination indicated a pT1a tumor of the tub2 type, with dimensions of 120 mm by 42 mm. Importantly, all assessments, including ulcer (UL), lymphatic (LY, vascular (V), histological margin (HM), and vascular margin (VM), returned negative results, suggesting no further spread of the cancer. However, post-surgery, the patient experienced gastric stenosis, necessitating additional interventions, which included the placement of a nutritional tube and dilation of the stenosis to alleviate symptoms. The intraoperative strategies employed during the ESTD procedure, along with coordinated care and psychological support throughout the recovery process, played a crucial role in helping the patient regain confidence. This comprehensive approach ultimately contributed to satisfactory outcomes in his recovery journey.ConclusionIn conclusion, ESTD offers a safer and more effective alternative to traditional methods in specific cases, especially for patients with large or challenging gastric lesions who favor a minimally invasive approach.